Answer:
![g(x)=4(3)^{x+1}+8](https://tex.z-dn.net/?f=g%28x%29%3D4%283%29%5E%7Bx%2B1%7D%2B8)
Step-by-step explanation:
Given:
The original function is given as:
![f(x)=2(3)^{x+1}+4](https://tex.z-dn.net/?f=f%28x%29%3D2%283%29%5E%7Bx%2B1%7D%2B4)
The above function is stretched vertically by a factor of 2 to form the graph of
.
According to the rule of function transformations, when the graph of a function is stretched in the vertical direction by a factor of 'C', where, 'C' is a number greater than 1, then the function rule is given as:
![f(x)\to Cf(x)](https://tex.z-dn.net/?f=f%28x%29%5Cto%20Cf%28x%29)
Therefore, the function is multiplied by a factor of 'C' to get the equation of the stretched function.
Here, the the value of 'C' is 2. So, the equation of
is given as:
![g(x)=2f(x)\\g(x)=2[2(3)^{x+1}+4]\\g(x)=4(3)^{x+1}+8](https://tex.z-dn.net/?f=g%28x%29%3D2f%28x%29%5C%5Cg%28x%29%3D2%5B2%283%29%5E%7Bx%2B1%7D%2B4%5D%5C%5Cg%28x%29%3D4%283%29%5E%7Bx%2B1%7D%2B8)
Therefore, the equation of
is
.